Complete mitochondrial genome and microsatellite marker development of the Antarctic scallop (Adamussium colbecki) for its population genetics analysis - Hye Jin Park; Soon Young Hwang; Hee-kyu Choi; Seo Yeon Byeon; Young Wook Ko; Sang Rul Park; Sanghee Kim; Hyuk Je Lee (PLoS ONE, 2026)
Adamussium colbecki is an ecologically important species (class Bivalvia) endemic to the Southern Ocean, but genomic resource for this species has remained yet limited. In this study, we first report the complete and annotated mitochondrial genome of A. colbecki , assembled using MGI paired-end sequencing. The circular mitogenome was 15,269 bp in length and comprised of 12 protein-coding genes (PCGs), two rRNA genes, and 18 tRNAs, with the atp8 gene absent, as commonly observed in bivalve molluscs. Phylogenetic analysis based on 11 mitochondrial PCGs (7,053 bp) revealed that A. colbecki formed a distinct and well-supported lineage within Pectinidae, the most closely related to Placopecten magellanicus . The 12S and 16S rRNA regions of the mitogenome were analyzed as mitochondrial DNA markers. In addition, using whole nuclear genomic information 144,512 perfect microsatellite loci (SSRs) were identified, and 30 primer-pairs were designed, among which seven polymorphic markers were developed. We then tested for their applicability to population genetics analysis and found that they were relatively highly polymorphic. These newly generated genomic resources will provide versatile genetic markers for future studies on population structure, genetic diversity, and evolutionary (demographic) history of A. colbecki , contributing to long-term population monitoring and conservation in the Antarctic marine ecosystem.